PENERAPAN ANALYTIC HIERARCHY PROCESS UNTUK PEMILIHAN SCOOTER MATIC - Setiawan, Santoso (LPPM Universitas Nusa Mandiri, 2013)
Urban road congestion and rising fuel prices make transportation mode users think hard to deal with this situation. This problem makes motor vehicle manufacturers, especially motorbikes, make superior products called scooter matic. This vehicle has the shape and capacity of the engine that is not too large and automatic coupling so that it is fuel efficient and very agile to maneuver in dense urban areas. At present each manufacturer of two-wheeled motorized vehicles has superior scooter matic products to attract consumers. This certainly can confuse ordinary consumers who want to have an automatic scooter. This study aims to give consideration to consumers so that they can help take the right decisions using the Analytical Hierarchy Process method. The results of the research are described in the form of percentage values adjusted to general objectives, criteria, sub-criteria, and strategic alternatives.